Corpus Luteum Development and Function after Supplementation of Long-Acting Progesterone During the Early Luteal Phase in Beef Cattle - Pugliesi, G.; Oliveria, Ml; Scolari, Sc; Lopes, E.; Pinaffi, Fv; Miagawa, Bt; Paiva, Yn; Maio, Jrg; Nogueira, Gp; Binelli, M. (Wiley, 2013)
Contents: Strategic supplementation of P4 may be used to increase conception rates in cattle, but timing of supplementation in relation to ovulation, mass of supplementary P4 and formulation of the P4-containing supplement has not been determined for beef cattle. Effects of supplementation of long-acting progesterone (P4) on Days 2 or 3 post-ovulation on development, function and regression of corpus luteum (CL) were studied in beef cattle. Cows were synchronized with an oestradiol/P4-based protocol and treated with 150 or 300 mg of long-acting P4 on Day 2 or 3 post-ovulation (6-7 cows/group). Colour-doppler ultrasound scanning and blood sample collection were performed from Day 2-21.5. Plasma P4 concentrations were greater (p < 0.05) from Day 2.5-5.5 in the Day 2-treated groups and from Day 3.5-5.5 in the Day 3-treated cows than in the control group. CL area and blood flow during Day 2-8.5 did not differ (p > 0.05) among groups, suggesting no effect of P4 treatment on luteal development. The frequency of cows that began luteolysis before Day 15 was greater (p < 0.04) in cows treated with 300 mg than in the controls, but there were no differences between non-treated and 150 mg-treated cows. The interval from pre-treatment ovulation to functional and structural luteolysis was shorter (p < 0.01) in the combined P4-treated groups than in the control cows. In conclusion, was showed for the first time that long-acting P4 supplementation on Day 2 or 3 post-ovulation increases P4 concentrations for ≥3 day, has no effect on luteal development, but anticipates the beginning of luteolysis in beef cattle. © 2013 Blackwell Verlag GmbH.